Attachment-based family therapy for sexual and gender minority young adults and their nonaccepting parents - Diamond, Gary M.; Boruchovitz-Zamir, Rotem (American Psychological Association, 2023)
"Many parents experience fear, shame, and loss upon learning that their child is same-sex oriented or gender non-conforming. Therapies to help parents become more accepting and foster meaningful relationships with their LGBTQ children are critical. Ongoing parental criticism, invalidation, and rejection of one's sexual or gender identity can take a profound psychological toll and lead to internalized homophobia, expectations for future gay-related rejection by others, depression, and other negative impacts. In contrast, parental acceptance is associated with lower rates of suicidal thoughts and suicide attempts, higher self-esteem, higher levels of perceived social support, lower levels of psychological symptoms, and better general health. While most parents become more accepting, or at least more tolerant, over time, others remain partially or fully rejecting even years after learning of their child's identity. Attachment-based family therapy for sexual and gender minority young adults (ABFT-SGM) helps reduce parental rejection, facilitate parental acceptance, and ultimately promote safer, closer, and more mutually respectful relationships between LGBTQ young adults and their parents. This informative book combines step-by-step guidance, real-life examples, and an empirically based approach to help therapists conduct transformative attachment experiences to keep these families connected"-- Provided by publisher.